Physiological and Biochemical Responses to Salt Stress in Cultivated Eggplant (Solanum melongena L.) and in S. insanum L., a Close Wild Relative - Brenes, Marco; Solana, Andrea; Boscaiu, Monica; Fita, Ana; Vicente, Oscar; Calatayud, Ángeles; Prohens, Jaime; Plazas, Mariola (MDPI, 2020)
Eggplant (Solanum melongena) has been described as moderately sensitive to salinity. We characterised the responses to salt stress of eggplant and S. insanum, its putative wild ancestor. Young plants of two accessions of both species were watered for 25 days with an irrigation solution containing NaCl at concentrations of 0 (control), 50, 100, 200, and 300mM.Plant growth, photosynthetic activity, concentrations of photosynthetic pigments, K+, Na+, and Cl􀀀 ions, proline, total soluble sugars, malondialdehyde, total phenolics, and total flavonoids, as well as superoxide dismutase, catalase, and glutathione reductase specific activities, were quantified. Salt stress-induced reduction of growth was greater in S. melongena than in S. insanum. The photosynthetic activity decreased in both species, except for substomatal CO2 concentration (Ci) in S. insanum, although the photosynthetic pigments were not degraded in the presence of NaCl. The levels of Na+ and Cl􀀀 increased in roots and leaves with increasing NaCl doses, but leaf K+ concentrations were maintained, indicating a relative stress tolerance in the two accessions, which also did not seem to su er a remarkable degree of salt-induced oxidative stress. Our results suggest that the higher salt tolerance of S. insanum mostly lies in its ability to accumulate higher concentrations of proline and, to a lesser extent, Na+ and Cl􀀀. The results obtained indicate that S. insanum is a good candidate for improving salt tolerance in eggplant through breeding and introgression programmes.